(untitled) - Majda, Andrew (Cambridge, 2002)
This comprehensive introduction to the mathematical theory of vorticity and incompressible flow begins with the elementary introductory material and leads into current research topics
Keywords: Vortex-motion,Non-Newtonian fluids,Chuyển động Vortex